Analytical and bioanalytical assessments of organic micropollutants in the Bosna River using a combination of passive sampling, bioassays and multi-residue analysis - Toušová, Zuzana; Vrana, Branislav; Smutná, Marie; Novák, Jiří; Klučárová, Veronika; Grabic, Roman; Slobodník, Jaroslav; Giesy, John Paul; Hilscherová, Klára (The Science of the total environment, 2019)
Complex mixtures of contaminants from multiple sources, including agriculture, industry or wastewater enter aquatic environments and might pose hazards or risks to humans or wildlife. Targeted analyses of a few priority substances provide limited information about water quality. In this study, a combined chemical and effect screening of water quality in the River Bosna, in Bosnia and Herzegovina was carried out, with focus on occurrence and effects of contaminants of emerging concern. Chemicals in water were sampled at 10 sites along the Bosna River by use of passive sampling. The combination of semipermeable membrane devices (SPMDs) and polar organic chemical integrative samplers (POCIS) enabled sampling of a broad range of contaminants from hydrophobic (PAHs, PCBs, OCPs) to hydrophilic compounds (pesticides, pharmaceuticals and hormones), which were determined by use of GC-MS and LC-MS (MS). In vitro, cell-based bioassays were applied to assess (anti)androgenic, estrogenic and dioxin-like potencies of extracts of the samplers. Of a total of 168 targeted compounds, 107 were detected at least once. Cumulative pollutant concentrations decreased downstream from the city of Sarajevo, which was identified as the major source of organic pollutants in the area. Responses in all bioassays were observed for samples from all sites. In general, estrogenicity could be well explained by analysis of target estrogens, while the drivers of the other observed effects remained largely unknown. Profiling of hazard quotients identified two sites downstream of Sarajevo as hotspots of biological potency. Risk assessment of detected compounds revealed, that 7 compounds (diazinon, diclofenac, 17β-estradiol, estrone, benzo[k]fluoranthene, fluoranthene and benzo[k]fluoranthene) might pose risks to aquatic biota in the Bosna River. The study brings unique results of a complex water quality assessment in a region with an insufficient water treatment infrastructure.
Keywords: polycyklické aromatické uhlovodíky; dioxiny; polychlorované bifenyly; polychlorované dibenzodioxiny; pesticidy; biotest; Polychlorinated Dibenzodioxins; Bosna a Hercegovina; Contaminants of emerging concern - passive sampling; Endocrine Disruptors; Environmental Monitoring; Dioxins; řeky; Polycyclic Aromatic Hydrocarbons; Hazard profiling - water quality monitoring; Wastewater; Rivers; Pesticides; monitorování životního prostředí; endokrinní disruptory; Waste Water; In vitro bioassay - endocrine disruption; Biological Assay; organické látky; estrogeny; Estrogens; Organic Chemicals; Water Pollutants, Chemical; Bosnia and Herzegovina; odpadní voda; Polychlorinated Biphenyls; chemické látky znečišťující vodu